Effects of inter-stimulus interval (ISI) duration on the N1 and P2 components of the auditory event-related potential - Diana R Pereira (2014)
The N1 and P2 components of the event-related potential are relevant markers in the processing of auditory information, indicating the presence of several acoustic phenomena, such as pure tones or speech sounds. In addition, the expression of these components seems to be sensitive to diverse experimental variations. The main purpose of the present investigation was to explore the role of inter-stimulus interval (IS!) on the N1 and P2 responses, considering two widely used experimental paradigms: a single tone task (1000 Hz sound repeated in a fixed rhythm) and an auditory oddball (80% of the stimuli were equal to the sound used in the single tone and the remaining were a 1500 Hz tone). Both tasks had four different conditions, and each one tested a fixed value of IS! (600, 1000, 3000, or 6000 ms). A sample of 22 participants performed these tasks, while an EEG was recorded, in order to examine the maximum amplitude of the N1 and P2 components. Analysis of the stimuli in the single tone task and the frequent tones in the oddball task revealed a similar outcome for both tasks and for both components: N1 and P2 amplitudes were enhanced in conditions with longer ISIs regardless of task. This response pattern emphasizes the dependence of both the N1 and P2 components on the ISI, especially in a scenario of repetitive and regular stimulation. The absence of task effects suggests that the ISI effect reported may depend on refractory mechanisms rather than being due to habituation effects.